Peningkatan Keterampilan Injeksi Pasien Diabetes dengan Menggunakan Self Insulin Injection Simulation Tool (SIIST) - Nur Muji Astuti; Christina Yuliastuti; Imroatul Farida (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to identify the effectiveness of using the Self Insulin Injection Simulation Tool (SIIST) to improve insulin injection skills in Diabetes Mellitus patients. The method used is a pretest-posttest control group design. The results showed that the increase in the average skill score in the SIIST intervention group was higher than in the control group, and there was a significant difference (p-value 0.001). In conclusion, education using SIIST is effective in improving the injection skills of Diabetes Mellitus patients. Instruction using the media simulation tool makes it easier for Diabetes patients to practice self-injection correctly and correctly. Keywords: Diabetes, Injection, Insulin, Skills, Simulation Tool